Enhancing performance of Li-S cells using a Li-Al alloy anode coating - Kim, Hyea; Lee, Jung Tae; Lee, Dong-Chan; Oschatz, Martin; Cho, Won Il; Kaskel, Stefan; Yushin, Gleb (Electrochemistry Communications, 2013)
Thin lithium aluminum (Li-Al) alloy layer is formed on the lithium surface in order to mitigate the polysulfide shuttle phenomenon. The effect of curing temperature of the alloy on electrochemical performance is studied. Electrochemical tests show the ability of the alloy layer to stabilize polarization during plating/deplating of Li ions. Li-S cells with the alloy-coated Li anodes show batter rate capability, lower charge transfer resistance, improved cycle stability and higher coulombic efficiency, compared to bare Li anode. © 2013 Elsevier B.V.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Alloy anode; Aluminum; Cathode dissolution; Li-S battery; Polarization; Sulfur cathode